HUBUNGAN MINUM OBAT ANTI HIPERTENSI DENGAN MELAKUKAN KONTROL TEKANAN DARAH RUTIN PADA LANSIA - RADEN SITI MARYAM; TIEN HARTINI; ROSIDAWATI ROSIDAWATI (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Riau, 2015)
Hypertension is a disease characterized by above-normal blood pressure , usually does not cause symptom, it is often called the silent killer. An estimated 76 % cases of hypertension in people who have not been diagnosed, in this case a person does not know that he was suffering from hypertension. This study aimed to get an overview of the factors that affect blood pressure control in the elderly. Methods: The study was a non - experimental (observational) with cross-sectional approach. The population in this study were all elderly people who come on Posyandu Lansia in Puskesmas Pulogadung district, East Jakarta with sample of 46 respondents. Results and Discussion: There was a significant relationship between taking antihypertensive medication ; have a history of hypertension ; and long suffered from hypertension with blood pressure control routine (p = 0.004 ; p = 0.018 ; p = 0.026). The factors that most influence on the elderly to perform routine blood pressure control is taking antihypertensive medication (p = 0.014 and Exp (B) = 45.5). A controlled blood pressure can reduce the risk factors of cardiovascular disease. To keep improving and maintaining the quality of the elderly can be done through activities in Posyandu Lansia with health education, monitoring the elderly who suffer from hypertension, and peer group